Exploring the Role of English Movies in Language Learning: Senior High School Students' Perceptions - Ni Putu Wulan Dewayanti; Luh Putu Artini; I Putu Indra Kusuma (Jurnal Multidisiplin Indonesia, 2026)
English proficiency has become an essential skill in the 21st century, necessitating effective learning strategies that provide meaningful exposure to authentic language use. Conventional learning methods based primarily on textbooks may not always provide sufficient opportunities for students to experience natural communication contexts. English-language movies, as authentic audiovisual media, offer potential support for language learning by presenting real conversations, pronunciation, vocabulary, cultural expressions, and communication situations. This study aims to explore senior high school students' perceptions of the role of English-language movies in English learning, including the benefits gained, challenges encountered, and students' views regarding their use as a learning medium. This research employed a qualitative approach with a descriptive design. The participants were six 10th-grade students from a senior high school in Indonesia, selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using the Miles, Huberman, and Saldaña interactive model, consisting of data reduction, data presentation, and conclusion verification. The findings reveal that English-language movies contribute to vocabulary development, listening comprehension, pronunciation improvement, speaking confidence, and increased learning motivation. However, students experienced difficulties related to fast-paced dialogue, accent variation, idioms, slang, and cultural references. To overcome these challenges, students utilized subtitles, replayed scenes, consulted dictionaries, and sought additional explanations. In conclusion, English-language movies are perceived as an effective supplementary medium for English learning, as they provide authentic language exposure and encourage more engaging and independent learning experiences